SCIENTIFIC AND THEORETICAL ASPECTS OF WELFARE TERRITORIAL COMMUNITIES - SHUMEIKO, Stanislav; AVEDYAN, Lyudmyla (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article is devoted to the research of scientific and theoretical aspects of the well-being of territorial communities in the context of decentralization and local development. The theoretical foundation of the territorial community was studied and analyzed, namely, it was determined that the territorial community is a type of socio-economic system, the components of which are comprehensively interconnected, are located on a large territory and spend significant resources to ensure their own development. The state’s need to regulate the well-being of community residents requires the use of a functional regional management system. This ensures optimal interaction between regional authorities, local self-government bodies and the state. The rationale for determining the well-being of the territorial community is provided. The authors consider well-being as a complex indicator that includes economic development, social cohesion and environmental sustainability. The concept of the well-being of the population of the community is a dynamic and complex concept that combines social, economic, ecological, cultural, educational and security conditions determined by the community itself. The main characteristics that determine the well-being of the community are highlighted. The mutual coordination of various components of well-being is presented. Legal, economic, organizational and financial methods should be distinguished among the methods of regulating the development of territorial communities. The article analyzes the main internal and external factors affecting the well-being of communities, including resource management, human capital, government policy, and environmental challenges. Ways to increase the level of well-being through the development of the economy, improvement of the social sphere and the implementation of environmental initiatives have been identified. It is noted that the necessary result is the community’s achievement of a high level of well-being, which contributes to the realization of the development goals of each local resident and becomes a chain of communication that has a positive effect.